PHARMACOLOGICAL POTENTIAL OF NATURE-BASED THERAPY FOR PSYCHOLOGICAL WELL-BEING: A COMMUNITY INTERVENTION STUDY IN HULU SELANGOR, MALAYSIA (Lex localis - Journal of Local Self-Government, 2025)
This pilot study investigates the pharmacological potential of nature-based therapy (NBT) in enhancing psychological well-being among adults in Hulu Selangor, Malaysia. Using a quantitative research design, 35 participants (85.7% female, 14.3% male) engaged in structured nature interventions, with psychological outcomes measured pre- and post-intervention using the Depression, Anxiety and Stress Scale (DASS-21) and program evaluation questionnaires. Results demonstrated significant improvements in mental health, with 77.1% of participants strongly agreeing that NBT enhanced their psychological well-being and 68.6% reporting better emotional stability. Additionally, the program fostered environmental stewardship, as 68.6% of participants adopted eco-friendly practices, and strengthened community engagement, with 71.4% actively participating in green initiatives. Despite limitations such as a small sample size and gender imbalance, the findings suggest that NBT is an effective, culturally relevant intervention for addressing mental health challenges in semi-urban Malaysian communities. The study highlights the dual benefits of NBT in improving individual well-being while promoting environmental awareness and social cohesion. These results support the integration of nature-based approaches into public health strategies, particularly in rapidly urbanizing regions. Future research should explore long-term effects, biomarker correlations, and strategies to enhance male participation in such programs.